Hubungan Status Gizi, Tingkat Stres dan Aktifitas Fisik dengan Siklus Menstruasi Tidak Normal Remaja Putri di MTs NEGERI 13 JAKARTA - Risya Aulia Oktaviani; Nur Asiah; Ana Utami Zainal (Sehat Rakyat: Jurnal Kesehatan Masyarakat, 2023)
The menstrual cycle is a sign of the process of maturity of the reproductive organs that are influenced by the body's hormones. Along the way, not all teenagers who have menstruation will go smoothly without complaints. Many factors can affect the menstrual cycle, for example, such as nutritional status, stress levels and physical activity. The purpose of this study was to determine the relationship between nutritional status, stress levels and physical activity with the menstrual cycle in adolescent girls at MTs Negeri 13 Jakarta in 2021. The type of research used is descriptive analytic with a cross sectional study design.  The total population in this study was all grade VIII and IX students at MTs Negeri 13 Jakarta, with a sample of 122 people using the Stratified random sampling technique. The instrument used was a questionnaire in the form of a google form that was distributed online  and the data analysis used was univariate and bivariate analysis with a chi square test. The results of the statistical test show that there is a relationship between Nutritional Status, Stress Level and Physical Activity with the menstrual cycle of adolescent girls in MTs Negeri 13 Jakarta in 2023. Based on this research, the researchers suggest bringing in health workers to MTs Negeri 13 Jakarta to provide counseling, knowledge, and understanding to young women about the menstrual cycle